2018
DOI: 10.1007/s00590-018-2229-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcomes of epidural steroids versus placebo after lumbar discectomy in lumbar disc herniation: a systematic review and meta-analysis of randomized controlled trials

Abstract: Treatment for lumbar disc herniation after failed conservative treatment is discectomy. Discectomy can significantly relieve back pain as well as radicular symptoms. However, many patients with lumbar discectomy experience moderate-to-severe back pain and radicular leg pain. The results of application of epidural steroids (ES) for pain management after lumbar discectomy have previously been inconclusive. We have conducted a systematic review and meta-analysis aims to compare outcomes (efficacy and complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
2
15
1
Order By: Relevance
“…However, the other studies reported a positive effect of steroids on pain. Four previous meta-analyses were published [ 18 21 ] ; 2 meta-analyses reported that intraoperative ESI when compared to placebo was effective in reducing pain in the early stage and reducing consumption of analgesia with no statistically significant differences in terms of overall complications and infection in lumbar discectomy. [ 18 , 19 ] One meta-analysis reported that intraoperative ESI application offers some benefits in pain control with a significant reduction in the length of hospital stay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the other studies reported a positive effect of steroids on pain. Four previous meta-analyses were published [ 18 21 ] ; 2 meta-analyses reported that intraoperative ESI when compared to placebo was effective in reducing pain in the early stage and reducing consumption of analgesia with no statistically significant differences in terms of overall complications and infection in lumbar discectomy. [ 18 , 19 ] One meta-analysis reported that intraoperative ESI application offers some benefits in pain control with a significant reduction in the length of hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] The most recent meta-analysis indicated a lower back and leg pain score, decreased morphine consumption, and shorter hospital stay without difference in complications for ESI application compared to placebo after lumbar discectomy in lumbar disc herniation that was not detected in previous meta-analyses. [ 21 ] However, these meta-analyses still have many limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Arirachakaran et al in his meta-analysis of use of epidural local steroid after discectomy showed decreased consumption of opioids in postoperative phase. 8 There was no difference in the complications between steroid and placebo group. Devi et al in his study of 61 patients with intraoperative use of steroid after lumbar discectomy found significant pain relief during postoperative days with less use of opioids but there was no difference in pain on long run and there was no difference in the complication rate.…”
Section: Discussionmentioning
confidence: 82%
“…Re.view of randomized control trials by Waqas favored intra operative use of steroids for lumbar disc surgery as it did improve pain in the post-operative period with fewer complications 14 . In spite of reported benefits including earlier mobilization, reduced requirement of post-operative pain killers and earlier discharge from the hospital, the technique is not employed routinely amongst the neurosurgeons 15 . One possible reason is that the efficacy is still controversial and is supported by subjective measures of outcome improvement only 16 .…”
Section: Discussionmentioning
confidence: 99%